StonePT: More than a brand, the reliability of excellence in dimension stones from Portugal - Lopes, Luís (2018)
StonePT – Portuguese Stone Brand objective is to certify the Natural Stone product, so that StonePT companies can technically communicate their products, with customers and prescribers, being easily identified through its BRAND, its Identity – STONEPT. The StonePT brand is supported by a certification system, aiming at the international recognition of Portuguese natural stone construction products, not only for its physical and mechanical characteristics, but also for the Portuguese transformer knowledge. This certification system, based on technical specifications and harmonized European standards for construction products using natural stone, aims at fulfilling a market gap with regard to guarantee of origin and quality assurance associated with the processing and , not least, the suitability of using each type of stone for different applications. StonePT consists of a signature that distinguishes the Portuguese Stone from all Products of the competition, using independent and credible stamps and certificates – internationally – for the recognition of Portuguese Stone as a contemporary quality product. What does it mean to be StonePT? It represents a national value. Or better still, it represents national values. This is why we have captured the Portuguese soul to show what it means to be the hallmark of the Portuguese ornamental stone. The Portuguese Stone Brand presents itself with an international communication strategy, inspired by Portugal. Allusive to the slogan “We offer the Best (from Portugal to the World)”, which is a declaration of Portuguese singularity, values and Portuguese raw material. Fado, football, sea and wine, ambassadors of the Portuguese name on the planet, meet the most varied types of national ornamental stones for a true celebration of what is Portuguese.